Atmospheric Levels of Benzene and C1-C2 Carbonyls in San Nicolas de los Garza, Nuevo Leon, Mexico: Source Implications and Health Risk - Cerón Bretón, Julia Griselda; Cerón Bretón, Rosa María; Kahl, Jonathan D.W.; Lara Severino, Reyna del Carmen; Ramírez Lara, Evangelina; Espinosa Fuentes, María de la Luz; Rangel Marrón, Marcela; Uc Chi, Martha Patricia (2017)
Abstract: AtmosphericbenzeneandcarbonylswerestudiedinSanNicolasdelosGarza,NuevoLeon, during 2011 and 2012. The relative abundance for measured VOCs was the following: formaldehyde (9.06 µgm−3)>acetaldehyde(8.06 µgm−3)>benzene(0.65 µgm−3). AllmeasuredVOCshadaclear seasonal trend with higher values of concentration during summer. Benzene and formaldehyde had a marked diurnal trend with the highest levels during morning, whereas acetaldehyde did not show a clear diurnal pattern. Meteorological analysis showed that the dominant winds came from NNE and ENE, suggesting that sources located in these directions contribute to the VOC levels. Principal component analysis (PCA) analysis revealed that photochemical activity inﬂuenced benzene and carbonyl levels during summer and that benzene was associated with vehicular trafﬁc emissions during autumn and winter, showing good correlation with CO. Meteorological data showed that measured VOCs were inﬂuenced by regional sources. A health risk assessment showed that local exposure to carbonyls and benzene exceeded 1×10−6 for integrated lifetime cancer risk. People living in San Nicolas de los Garza, thus, have a probable risk of suffering cancer in their lifetime. It is, therefore, necessary to improve environmental policies for controlling VOC levels in this area. Keywords: VOCs; benzene; carbonyls; atmospheric pollution; health risk; Mexico